2010
DOI: 10.4049/jimmunol.1001707
|View full text |Cite
|
Sign up to set email alerts
|

A Cell-Impermeable Cyclosporine A Derivative Reduces Pathology in a Mouse Model of Allergic Lung Inflammation

Abstract: Although the main regulators of leukocyte trafficking are chemokines, another family of chemotactic agents is cyclophilins. Intracellular cyclophilins function as peptidyl-protyl cis-trans isomerases and are targets of the immunosuppressive drug, cyclosporine A (CsA). Cyclophilins can also be secreted in response to stress factors, with elevated levels of extracellular cyclophilins detected in several inflammatory diseases. Extracellular cyclophilins are known to have potent chemotactic properties, suggesting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 48 publications
(55 citation statements)
references
References 40 publications
3
52
0
Order By: Relevance
“…CD147 is a type I transmembrane glycoprotein, a member of the immunoglobulin super-family, that is expressed by a wide array of cell types, including epithelial, endothelial and hematopoietic cells (6). CD147 is a signaling receptor for extracellular cyclophilins (Cyp) A and B (7,8), and recent publications have identified the CD147 signaling pathway induced by extracellular cyclophilins as a triggering mechanism regulating MMP expression and inflammation in atherosclerosis, rheumatoid arthritis, allergic and chronic lung disease (9)(10)(11)(12)(13)(14). Thus, we hypothesized that CD147 activation by extracellular cyclophilin may play a role in experimental BA as well.…”
Section: Targeting Extracellular Cyclophilins Ameliorates Disease Promentioning
confidence: 99%
See 1 more Smart Citation
“…CD147 is a type I transmembrane glycoprotein, a member of the immunoglobulin super-family, that is expressed by a wide array of cell types, including epithelial, endothelial and hematopoietic cells (6). CD147 is a signaling receptor for extracellular cyclophilins (Cyp) A and B (7,8), and recent publications have identified the CD147 signaling pathway induced by extracellular cyclophilins as a triggering mechanism regulating MMP expression and inflammation in atherosclerosis, rheumatoid arthritis, allergic and chronic lung disease (9)(10)(11)(12)(13)(14). Thus, we hypothesized that CD147 activation by extracellular cyclophilin may play a role in experimental BA as well.…”
Section: Targeting Extracellular Cyclophilins Ameliorates Disease Promentioning
confidence: 99%
“…Therefore, specific targeting of extracellular cyclophilins may be a valid therapeutic strategy to inhibit CD147-dependent pathways. MM284 is a nonimmunosuppressive cell-impermeable cyclosporine derivative that does not penetrate the plasma membrane and, therefore, cannot interact with intracellular cyclophilins and mediate intracellular immunosuppressive activity; thus MM284 targets only the extracellular pool of cyclophilins (12,18). We hypothesized that the liver inflammation associated with BA may be induced or activated by the interaction of extracellular CypA with CD147 located at the plasma membrane of hepatocytes and hepatic stellate cells, and blocking this interaction by MM284 would inhibit this inflammatory response and subsequent liver inflammation and, potentially, fibrosis.…”
Section: Targeting Extracellular Cyclophilins Ameliorates Disease Promentioning
confidence: 99%
“…Use of NIM811 instead of parent compound, cyclosporine A, allowed eliminating a confounding effect of immunosupression on atherosclerosis, limiting the effects of inhibition of cyclophilins. Each compound was administered every second day by intraperitoneal injection at a dose of 6.6 mg/kg; we previously found that this dose inhibited allergic lung inflammation (Balsley et al, 2010). Control mice were injected with vehicle (15% ethanol in 15% cremophore EL).…”
Section: Resultsmentioning
confidence: 99%
“…In this study we tested a hypothesis that selective inhibition of extracellular activities of cyclophilins without affecting their intracellular activities, an approach proven beneficial in allergic lung inflammation (Balsley et al, 2010), may achieve separation of proatherogenic from antiatherogenic effects of cyclophilin inhibition. This anticipation was based on predominantly proinflammatory activities exerted by extracellular cyclophilins (Bukrinsky, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Nonimmunosuppressive cyclosporin derivatives have reached clinical development for the treatment of hepatitis C infection. 20 Moreover, formulations of cyclosporin have also shown some promise in new therapeutic applications, for example, in traumatic brain injury, 21 muscular dystrophy, 22 respiratory diseases, 23 cardiovascular diseases, 24 and Alzheimer's disease. 25 Much effort is spent on selecting specific PPIase modulators for therapeutic approaches, and in this framework, the discovery of novel inhibitors may largely benefit from suitable assays for HTS.…”
Section: Discussionmentioning
confidence: 99%